1995
DOI: 10.1007/bf00196366
|View full text |Cite
|
Sign up to set email alerts
|

Listvenite and related rocks: perspectives on terminology and mineralogy with reference to an occurrence at Cregganbaun, Co. Mayo, Republic of Ireland

Abstract: Abstract. The rock 'listvenite' is named and defined by reference to historical observations and recommendations are made so that listvenite (s.s.) can be distinguished from related carbonate-rich alteration products of ultramafic rocks. The mineralogy and tectonic setting of listvenite are reviewed, taking into account the descriptions and classifications used in the literature. The petrography of listvenite and related rocks at Cregganbaun serves as a reference to illustrate the characteristics of true listv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
82
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 28 publications
(45 reference statements)
2
82
0
1
Order By: Relevance
“…1996, 2000). Because, Cr-mica (fuchsite) is absent in the metasomatites of the study area, the alteration assemblages of Mihalıççık region are not proper listvenites but members of the listvenitic series with respect to the description of Halls and Zhao (1995).The temporal phase relations indicate a primary stage of carbonatization that took place before the subsequent silicification. The spatial distribution of the alteration products are not apparent in all of the outcrops; however, in Türkmen Oturaǧı district (Figure 2), thin section studies showed that the carbonate assemblages change into silicacarbonate rocks in the altered body northeastwards.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…1996, 2000). Because, Cr-mica (fuchsite) is absent in the metasomatites of the study area, the alteration assemblages of Mihalıççık region are not proper listvenites but members of the listvenitic series with respect to the description of Halls and Zhao (1995).The temporal phase relations indicate a primary stage of carbonatization that took place before the subsequent silicification. The spatial distribution of the alteration products are not apparent in all of the outcrops; however, in Türkmen Oturaǧı district (Figure 2), thin section studies showed that the carbonate assemblages change into silicacarbonate rocks in the altered body northeastwards.…”
mentioning
confidence: 93%
“…J. 41: 557-580 (2006) Copyright # 2006 John Wiley & Sons, Ltd. 1947Bok 1956;Ploshko 1963; Allakhverdiev 1965, 1971;Shcherban 1967;Shcherban and Borovikova 1969;Abovian 1978;Kuleshevich 1984;Ivan et al 1985;Buisson and Leblanc 1985, 1986Aydal 1989;Nixon 1990; Ash and Arksey 1990a,b;Madu et al 1990;Spiridonov 1991;Auclair et al 1993;Halls and Zhao 1995;Uçurum 1996Uçurum , 2000. Listvenites (quartz-carbonate-chromium mica association), quartz-carbonate rocks (silica-carbonate association), carbonate-rich rocks, serpentinetalc-(chlorite)-carbonate rocks, talc-carbonate rocks and talc-silica-carbonate rocks are the examples of the metasomatites.…”
mentioning
confidence: 97%
See 3 more Smart Citations